PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP MOTIVASI KERJA GURU DI SMA SE-KECAMATAN DAYEUHKOLOT - Dees Andriyana Sumadiharja, - (2021)
This research is entitled "The Influence of Transformational Leadership of Principals on Teacher Work Motivation in Senior High School in Dayeuhkolot Subdistrict". This research uses descriptive method and quantitative approach. The sampling technique used is Probability Sampling by proportionate stratified random sampling, with the population in this study as many as 143 teachers and samples of 59 teachers at 3 senior high schools in Dayeuhkolot subdistrict. The results of this study based on data processing conducted with Weight Means Score (WMS) calculations showed the average general tendency for Variable X (Transformational Leadership of Principals) and Variable Y (Teacher Work Motivation) to be in the category is very good. The result of the correlation coefficient test between variable X and variable Y obtained a positive result of 0.529 which shows that variable X and variable Y have a correlation. Variable X had an effect of 22.0% on Variable Y, while the remaining 78.0% was influenced by other factors not studied in the study. The result of a simple linear regression test showing Ŷ = 21.608 + 0.545X is significant and linear. Furthermore, the results of the correlation coefficient significance test showed that with the test of thitung > ttabel (4,005 > 1,678) then Ho was rejected and Ha was accepted. The conclusion of this study is the positive and significant influence between the transformational leadership of the principal on the motivation of teacher work in senior high school in Dayeuhkolot Subdistrict.